Travel patterns, risk behaviour and health problems of travellers with rheumatic diseases compared to controls: A multi-centre, observational study. Issue 38 (November 2020) - Schmid, Nathan; Ciurea, Adrian; Gabay, Cem; Hasler, Paul; Fehr, Jan; Müller, Rüdiger; Villiger, Peter; Walker, Ulrich; Hatz, Christoph; Bühler, Silja
Abstract: Background: Patients with chronic conditions travel around the world more than ever. Only few studies have examined travel patterns and health outcomes of patients with rheumatic diseases during international travel. Method: We conducted a multi-centre prospective cohort study in Switzerland, in which we studied the immunogenicity and safety of vaccinations in patients with rheumatic diseases and travellers without rheumatic diseases (controls). Participants who travelled internationally received questionnaires 1 and 13 weeks post-travel. We compared travel patterns, risk behaviours, and travel-associated problems during and after the trips in both groups. Results: 274 participants returned post-travel questionnaires (65 rheumatic patients, 209 controls). Controls more frequently travelled to subtropical/tropical destinations and stayed longer abroad. 64% of all participants experienced health problems during travel (74% rheumatic patients vs. 62% controls, P = 0.11). Pre-travel, patients reported a higher susceptibility to gastrointestinal infections . During travel, a higher percentage of rheumatic patients cancelled the day programme due to health problems (13% vs. 4%, P = 0.024). The main problems in rheumatic patients occurred due to the underlying rheumatic diseases, or were of psychological nature. Although not statistically significant, infectious disease symptoms (rhinitis, cough) occurred more frequently in controls. When only considering subtropical/tropical destinations, rheumatic patients more frequently had gastrointestinal problems during travel - and skin infections after the trip. Conclusions: This study does not support the notion that patients with rheumatic diseases should avoid international travel for an increased risk of infections. In patients with subtropical/tropical destinations, however, gastrointestinal problems may be increased during travel - and skin infections post-travel.